TRAIL modulates the immune system and protects against the development of diabetes. - Bossi, Fleur; Bernardi, Stella; Zauli, Giorgio; Secchiero, Paola; Fabris, Bruno (J Immunol Res, 2015)
TRAIL or tumor necrosis factor (TNF) related apoptosis-inducing ligand is a member of the TNF superfamily of proteins, whose best characterized function is the induction of apoptosis in tumor, infected, or transformed cells through activation of specific receptors. In nontransformed cells, however, the actions of TRAIL are less well characterized. Recent studies suggest that TRAIL may be implicated in the development and progression of diabetes. Here we review TRAIL biological actions, its effects on the immune system, and how and to what extent it has been shown to protect against diabetes.
Keywords: Animals; Diabetes Mellitus; Humans; Immune System; Receptors, TNF-Related Apoptosis-Inducing Ligand; Signal Transduction